Hedges and Boosters in Undergraduate Students’ Research Articles - Imraatu Salichah; Enny Irawati; Yazid Basthomi (Pascasarjana UM, 2015)
Abstract: This study aims at investigating the use of hedges and boosters which are important in academic writing discourse as a mean of communicative strategies for increasing or reducing the force of statements. The data of this study were taken from the undergraduate students’ research ar-ticles of English Department at State University of Malang and analyzed based on the taxonomy of Hyland (1998a) and Hinkel (2005). The result showed that there were five types of hedges and three types of boosters. Moreover, the students used greater hedges than boosters in their research arti-cles as a way of reducing the risk of opposition, as a mean of being polite and as a way to obscure their authorial identity while advancing their opinion. However, the writers also used boosters to show their research originality and when they were quite sure that their claims share some universal understanding. Furthermore, the misused hedging devices by the students showed that they lack of knowledge of English rhetoric.Key Words: hedges, boosters, articlesAbstrak: Penelitian ini bertujuan untuk menyelidiki penggunaan hedges dan boosters dalam menulis wacana akademik sebagai sarana strategi komunikatif untuk meningkatkan atau mengurangi kekuatan pernyataan. Data penelitian ini diambil dari artikel penelitian mahasiswa Jurusan Bahasa Inggris di Universitas Negeri Malang dan dianalisis berdasarkan taksonomi Hyland (1998a) dan Hinkel (2005). Hasil penelitian menunjukkan bahwa ada lima jenis hedges dan tiga jenis boosters. Selain itu, siswa menggunakan hedges memiliki nilai lebih besar dari boosters dalam artikel penelitian sebagai cara un-tuk mengurangi risiko oposisi, untuk menunjukkan sikap sopan dan untuk mengaburkan identitas kepenulisan dan menguatkan pendapat. Boosters juga digunakan untuk menunjukkan orisinalitas penelitian. Hedging yang disalahgunakan oleh para siswa menunjukkan bahwa kurangnya pengetahu-an tentang retorika bahasa Inggris.Kata kunci: hedges, boosters, artikel